Towards the replacement of wheat 'Green Revolution' genes. (2nd February 2021) - Pearce, Stephen
Abstract : This article comments on: Tang T, Botwright Acuña T, Spielmeyer W and Richards RA . 2021. Effect of gibberellin-sensitive Rht18 and gibberellin-insensitive Rht-D1b dwarfing genes on vegetative and reproductive growth in bread wheat. Journal of Experimental Botany 72, 445–458 .